Dosing and Safety Profile of Aficamten in Symptomatic Obstructive Hypertrophic Cardiomyopathy: Results From SEQUOIA‐HCM - Caroline J. Coats; Ahmad Masri; Michael E. Nassif; Roberto Barriales‐Villa; Michael Arad; Nuno Cardim; Lubna Choudhury; Brian Claggett; Hans‐Dirk Düngen; Pablo Garcia‐Pavia; Albert A. Hagège; James L. Januzzi; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Aficamten, a novel cardiac myosin inhibitor, reversibly reduces cardiac hypercontractility in obstructive hypertrophic cardiomyopathy. We present a prespecified analysis of the pharmacokinetics, pharmacodynamics, and safety of aficamten in SEQUOIA‐HCM (Safety, Efficacy, and Quantitative Understanding of Obstruction Impact of Aficamten in HCM). Methods and Results A total of 282 patients with obstructive hypertrophic cardiomyopathy were randomized 1:1 to daily aficamten (5–20 mg) or placebo between February 1, 2022, and May 15, 2023. Aficamten dosing targeted the lowest effective dose for achieving site‐interpreted Valsalva left ventricular outflow tract gradient <30 mm Hg with left ventricular ejection fraction (LVEF) ≥50%. End points were evaluated during titration (day 1 to week 8), maintenance (weeks 8–24), and washout (weeks 24–28), and included major adverse cardiac events, new‐onset atrial fibrillation, implantable cardioverter‐defibrillator discharges, LVEF <50%, and treatment‐emergent adverse events. At week 8, 3.6%, 12.9%, 35%, and 48.6% of patients achieved 5‐, 10‐, 15‐, and 20‐mg doses, respectively. Baseline characteristics were similar across groups. Aficamten concentration increased by dose and remained stable during maintenance. During the treatment period, LVEF decreased by −0.9% (95% CI, −1.3 to −0.6) per 100 ng/mL aficamten exposure. Seven (4.9%) patients taking aficamten underwent per‐protocol dose reduction for site‐interpreted LVEF <50%. There were no treatment interruptions or heart failure worsening for LVEF <50%. No major adverse cardiovascular events were associated with aficamten, and treatment‐emergent adverse events were similar between treatment groups, including atrial fibrillation. Conclusions A site‐based dosing algorithm targeting the lowest effective aficamten dose reduced left ventricular outflow tract gradient with a favorable safety profile throughout SEQUOIA‐HCM. Registration URL: https://www.clinicaltrials.gov; Unique Identifier: NCT05186818.